2021
DOI: 10.3390/foods10122969
|View full text |Cite
|
Sign up to set email alerts
|

The Conformational Structural Change of Soy Glycinin via Lactic Acid Bacteria Fermentation Reduced Immunoglobulin E Reactivity

Abstract: This study investigated the fermentation of isolated soy glycinin by using the Lactiplantibacillus plantarum B1-6 strain, its reduction effect on immunoglobulin E (IgE) reactivity, the relationship with protein aggregation/gelation state and conformational changes. Fermentation was performed under different glycinin concentrations (0.1%, 0.5%, 1% and 2%, w/v) and varied fermentation terminal pH levels (FT-pH) (pH 6.0, 4.5, 4.0 and 3.5). L. plantarum B1-6 showed potency in reducing immunoreactivity to 0.10–69.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…This might lead to the exposure of allergenic epitope degradation sites, thereby increasing the intensity of epitope degradation. 9 After 180 min of digestion, epitope-degradation frequency decreased. The most obvious reduction occurred in epitopes with β-sheet and α-helix structures.…”
Section: Food and Function Papermentioning
confidence: 99%
See 3 more Smart Citations
“…This might lead to the exposure of allergenic epitope degradation sites, thereby increasing the intensity of epitope degradation. 9 After 180 min of digestion, epitope-degradation frequency decreased. The most obvious reduction occurred in epitopes with β-sheet and α-helix structures.…”
Section: Food and Function Papermentioning
confidence: 99%
“…6 Our previous research has revealed that Lactobacillus plantarum B1-6 fermentation significantly reduces the antigenicity of glycinin, and the effect varies with the glycinin concentration and fermentation terminal pH. 9…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations